Evaluation of the Effect of a Dental Simulation App on Anxiety in Pediatric Dental Patients Undergoing Restorative Treatment: A Randomized Controlled Trial - Dr. Rushita Shah; Dr. Mahesh D R; Dr. Anitta Rachel Saju; Dr. Sejal Modi; Dr. Shubhangi Pareek; Dr. Shreeyam Mohapatra (The Bioscan, 2025)
Aim: This study aimed to explore the impact of a dental treatment simulation app on anxiety levels in pediatric dental patients. Materials and Methods: A total of thirty children, aged 4 to 8 years old and without previous dental experiences, were randomly divided into two groups: the control group (Group I) and the dental app group (Group II). Anxiety levels were assessed before and after restorative dental treatment using the RMS pictorial scale (RMS-PS). Results: Both groups displayed similar initial anxiety levels. However, post-treatment analysis revealed that the dental app group experienced a significant reduction in anxiety compared to the control group. This finding indicates that the simulation app effectively alleviates dental anxiety in children. Conclusion: The dental treatment simulation app proves to be effective in reducing both pre- and postoperative anxiety in pediatric patients, potentially improving their overall dental experience.